Application of the Theory of Planned Behavior to Predict Nutrition Students' Intention to Work with Older Adults. Issue 1 (2nd January 2020) - Jung, Seung Eun; Lawrence, Jeannine; Hermann, Janice; McMahon, Amy
Abstract: As Registered Dietitian Nutritionists play an important role in providing nutrition care plans for successful aging, it is important to identify factors influencing nutrition students' intention to work with older adults. A cross-sectional study was conducted to identify significant predictors of nutrition students' intention to work with older adults by utilizing the Theory of Planned Behavior (TPB). A total of 183 students, majoring in Nutrition at a large Southern University, completed a questionnaire examining validated TPB constructs. Structural Equation Modeling with maximum likelihood was used to analyze the data. The structural model provided a good fit to the data ( x 2  = 44.95, df  = 38, p  < 0.01; RMSEA  = 0.03, CFI  = 0.99; TLI  = 0.99. Attitude ( γ  = 0.49, p  < 0.001) and subjective norm ( γ  = 0.39, p  < 0.001) emerged as significant predictors of nutrition students' intention to work with older adults. Findings highlight the importance of providing dietetics curricula that provide opportunities for students to develop positive attitudes toward working with older adults. Dietetic educators should present themselves as positive role models in working with older adults, as the educators influence students' intention to work with this population.